Proceedings of the 6th Intl Symposium on Modeling and Optimization 2008
DOI: 10.4108/icst.wiopt2008.2982
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the IEEE 802.15.4 MAC Protocol for Scalable Data Collection in Dense Sensor Networks

Abstract: We find that the IEEE 802.15.4 MAC protocol performs poorly for one-hop data collection in dense sensor networks, showing a steep deterioration in both throughput and energy consumption with increasing number of transmitters. We propose a channel feedback-based enhancement to the protocol that is significantly more scalable, showing a relatively flat, slowchanging total system throughput and energy consumption as the network size increases. A key feature of the enhancement is that the back-off windows are upda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 14 publications
1
41
0
Order By: Relevance
“…Different from most solutions available in the literature, our approach is specifically suited for the IEEE 802.15.4 and ZigBee standards. In contrast with many approaches such as [12], our scheme does not require any modification to the IEEE 802.15.4 MAC protocol, and hence can be implemented in real sensors even when the MAC protocol cannot be altered. Furthermore, unlike [7], [6], our scheme is adaptive, hence it can tailor the operating parameters -e.g., the backoff window size and the number of (re)transmissions -according to the actual traffic demands.…”
Section: A Our Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different from most solutions available in the literature, our approach is specifically suited for the IEEE 802.15.4 and ZigBee standards. In contrast with many approaches such as [12], our scheme does not require any modification to the IEEE 802.15.4 MAC protocol, and hence can be implemented in real sensors even when the MAC protocol cannot be altered. Furthermore, unlike [7], [6], our scheme is adaptive, hence it can tailor the operating parameters -e.g., the backoff window size and the number of (re)transmissions -according to the actual traffic demands.…”
Section: A Our Contributionsmentioning
confidence: 99%
“…In the context IEEE 802.15.4-based WSNs, many papers [12], [13], [14] highlighted that a significant share of transmitted messages may be lost due to contention, especially when the number of sensor nodes and the message size are large. In addition, [6] and [7] have shown that serious reliability issues arise when power management is enabled, even in networks with a small number of sensor nodes.…”
Section: Related Workmentioning
confidence: 99%
“…However, in the p-persistent CSMA/CA, the backoff interval is based on a geometric distribution with a specific probability of transmission, p. Therefore, the probability that a node stays idle when having a busy medium is 1 − p. The p-persistent CSMA/CA provides very close approximation to the IEEE 802.11 [48][50][51] [52], and the memoryless backoff property makes it suitable for the purpose of analysis.…”
Section: Adaptation To the Number Of Neighboring Nodesmentioning
confidence: 99%
“…Based on the defined probability of transmissions and since the packet length, L, is fixed, [52]. For maximum system performance in terms of throughput, the value of V T should be minimized.…”
Section: Adaptation To the Number Of Neighboring Nodesmentioning
confidence: 99%
“…This is called batched arrivals [5], where many nodes attempt to transmit packets at the same time, possibly resulting in severe collisions [6]. This type of data traffic appears in many sensor network applications [7]- [9]; it is called one-shot data (OSD) in [10]. For example, in many sensor network applications to monitor the environment, such as a bush fire detection system or a humidity monitoring system, when the temperature rises and exceeds a threshold near the fire itself, or humidity rises before rainfall, nearby nodes will be triggered and will simultaneously send one packet each.…”
Section: A Assumptionsmentioning
confidence: 99%